Antiproliferative Activities of Anthocephalus cadamba Extracts on Human Breast Cancer and Cervical Adenocarcinoma Cell Lines - Rita K Sari; Devi Armilasari; Deded S Nawawi; Wayan Darmawan; Silmi Mariya (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
The aim of this research was to evaluate the anticancer properties of methanolic extracts from inner bark and wood of jabon (Anthocephalus cadamba). The extracts were investigated in vitro bioassay for its possible antiproliferative activities on human MCF7 breast cancer cell line and HeLa cervical adenocarcinoma cell lines. The cell viability were assessed using microculture tetrazolium technique (MTT) colorimetric assay. The results showed that inner bark extract exhibited higher antiproliferative activity on MCF7 cancer cell line (IC50 91 μg ml-1) than wood extract (IC50 312 μg ml-1). But, antiproliferative activity of inner bark extract on HeLa cell lines was higher (IC50 5 μg ml-1). The inner bark extract is potential to be developed as anti cancer agent in cervical adenocarcinoma cancer therapy because moresecure against Vero normal cells (IC50 288 μg ml-1). Whereas compounds such as phenolic and fatty acid contribute to high antiproliferative activities of inner bark extract. The qualitative analysis detect the extracts containing flavonoids, triterpenoids, saphonin which are thought to contribute to the high antiproliferative activities of this extract.Keywords : Anthocephalus cadamba, antiproliferative activity, human MCF7 breast cancer cell line, HeLa cervical adenocarcinoma cell lines, Vero normal cell lines